Management of COVID-19-related post-intubation tracheal stenosis - Conforti, Serena; Licchetta, Gloria; Reda, Marco; Astaneh, Arash; Pogliani, Luca; Fieschi, Stefano; Rinaldo, Alessandro; Torre, Massimo (Frontiers in Surgery, 2023)
Introduction: Severe Acute Respiratory Syndrome Coronavirus 2 pandemic (SARS-COV-2) hit Italy since the beginning of 2020. Endotracheal intubation, prolonged mechanical ventilation and tracheostomy are frequently required in patients with severe COVID-19. Tracheal stenosis is a potentially severe condition that can occur as a complication after intubation. The aim of the study was to evaluate the utility and safety of the endoscopic and surgical techniques in the treatment of tracheal stenosis related to COVID 19. Materials and Methods: From June 2020 to May 2022, consecutive patients with tracheal stenosis who were admitted to our surgical Department were considered eligible for the study participation. Results: A total of 13 patients were included in the study. There were 9 females (69%) and 4 males (31%) with a 57,2 median age of years. We included 7 cases of post tracheostomy tracheal stenosis. Bronchoscopy is performed to identify the type, location and severity of the stenosis. All patients underwent bronchoscopic dilation and a surveillance bronchoscopy 7/30 days after procedure. We repeated endoscopic treatment in 8 patients. 3 patients underwent tracheal resection anastomosis. Final follow-up bronchoscopy demonstrated no residual stenosis. Conclusions: The incidence and risk factors associated with tracheal stenosis in critically ill patients with COVID-19 are currently unknown. In our experience, in case of relapsed tracheal stenosis it is confirmed the efficacy and the safety of endoscopic management followed by surgical procedures.